Cat’s external otitis - diagnose and treatment - Degi, J. (Medicamentul Veterinar)
Otitis externa is a frequent finding in cats, with a prevalence rate of 2-10 % of all feline patients seen in general practice. Otodectes cyanotis, the ear mite, is responsible for approximately 50% of all feline otitis externa cases. However, other infectious and inflammatory conditions frequently either cause or predispose the cat to ear disease. In 20-30 % of chronic feline ear cases the initiating cause remains unknown.